The history, current state and perspectives of aerosol therapy - ROSPOND, BARTŁOMIEJ; KRAKOWSKA, AGATA; MUSZYŃSKA, BOŻENA; OPOKA, WŁODZIMIERZ (Acta pharmaceutica (Zagreb, Croatia), 2022)
Nebulization is a very effective method of drug administration. This technique has been popular since ancient times when inhalation of plants rich in tropane alkaloids with spasmolytic and analgesic effects was widely used. Undoubtedly, the invention of anasthesia in the 19th century had an influence on the development of this technique. It resulted in the search for devices that facilitated anasthesia such as pulveriser or hydronium. From the second half of the 21st century, when the first DPI and MDI inhalers were launched, the constant development of aerosol therapy has been noticed. This is due to the fact that nebulization, compared with other means of medicinal substance application (such as oral and intravenous routes of administration), is safer and it exhibits a positive dose/efficacy ratio connected to the reduction of the dose. It enables drugs administration through the lung and possesses very fast onset action. Therefore, various drugs prescribed in respiratory diseases (such as corticosteroids, β-agonists, anticholinergics) are present on the market in a form of an aerosol.